The Issues of the Professional Crime Prevention in the Republic of Kazakhstan - RAKHIMBERLIN, Oirat Nurashovich (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
The presented article deals with the features of the professional crime prevention in the Republic of Kazakhstan. The author carries out an analysis of developing the phenomenon, which has been built up since the Russian Empire and then the USSR, therefore, the conditions, features and measures to prevent the professional crime are very similar in the CIS countries. At the same time, the author indicates some specifics, which is expressed in the professional manner of certain criminal activities due to the traditional way of life of the Kazakhstan’s population. The examples of the foreign experience in fighting against the professional crime have been studied. A complex of the special and general social measures to prevent the professional crime has been suggested, the mechanism has been thoroughly investigated, as well as the examples of the actions by the authorities and the society for the social integration of ex-offenders as an important factor in preventing the professional crime have been given.
Keywords: professional crime, criminal specialization, recidivism, preventive measures, social integration